Hepatology Center for the Management of Patients with Hepatitis: Proposed Electronic Health Record. - Tsakona, Anna; Paschali, Kallirroi; Tsolis, Dimitrios; Skapetis, Georgios (International Journal of Caring Sciences)
Introduction: The operation of the hepatology center is based on the use of a patient's health record. It is a printed record that the physician prepares and fills in at every visit of the patient, keeping in good order all information related to the patient's health problems and which concern mainly the liver problem. The way the printed record is kept and managed is a procedure that requires optimum organization, order and effort on the part of the medical personnel. In these efforts, ways to facilitate the procedure could be sought by using the new information and communication technologies. The aim of this paper is to depict the actual status and conditions under which the hepatology center of the PPGNP (University Regional General Hospital of Patras) currently operates. To identify the level of technological dissemination and to underline the benefits that the practice of medicine gains. Moreover, it aims at identifying the problems that doctors encounter in their attempt to organize their work and how the adoption of bioinformatics tools can prove helpful. Conclusions: This paper underlines the need to adopt the EHR and modern technologies that bioinformatics offers at all levels of practicing the medical profession in the Greek hospitals. Actually, taking into account the specialized needs of each department and each user, we shall only remain limited to the simple use of a computer or an EHR program, but we shall make all possible efforts to seek for those technologies that will bring a real change in the way we work and will yield the maximum benefits possible.